Wykonaj mnożenie:
b) (-8x + 6y² - 2y + x²) * (-6) =
c) (2,8s²w² + 6,4s² - 1,8w²) * 2,5sw =
d) (2/3p³ + 3/4 p² + 4/5p + 5/6) * 60p(potega 4) =
e) (-10gh + 20g - 30h) * (-0,1gh) =
f) (-1/2a + 1/4b² - 3a²b²) *4ab =

Prosze o pelne obliczenia a nie tylko wyniki

1

Odpowiedzi

2010-02-03T20:09:11+01:00
Wykonaj mnożenie:
b) (-8x + 6y² - 2y + x²) * (-6) =48x-36y²+12y-6x²
c) (2,8s²w² + 6,4s² - 1,8w²) * 2,5sw=7s³w³+16s³w-4,5sw³
d) (2/3p³ + 3/4 p² + 4/5p + 5/6) * 60p⁴ =40p⁷+45p⁶+48p⁵+50p⁴
e) (-10gh + 20g - 30h) * (-0,1gh) =1g²h²-2g²h+3gh²
f) (-1/2a + 1/4b² - 3a²b²) *4ab =-2a²b+1ab³-12a³b³
1 5 1